1942
DOI: 10.1090/s0002-9904-1942-07771-8
|View full text |Cite
|
Sign up to set email alerts
|

Table of the zeros of the Legendre polynomials of order 1-16 and the weight coefficients for Gauss’ mechanical quadrature formula

Abstract: Gauss' method of mechanical quadrature has the advantage over most methods of numerical integration in that it requires about half the number of ordinate computations. This is desirable when such computations are very laborious, or when the observations necessary to determine the average value of a continuously varying physical quantity are very costly. Gauss' classical result 2 states that, for the range (-1, +1), the "best" accuracy with n ordinates is obtained by choosing the corresponding abscissae at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1955
1955
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…We have also found that the appended program can compute the numerical integration formulas of orders ; 1 ≤ n ≤ 48 which agree with standard tables presented in [4][5][6][7]. We hope that the MATLAB program presented here will be a useful addition to the existing software on numerical integration.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…We have also found that the appended program can compute the numerical integration formulas of orders ; 1 ≤ n ≤ 48 which agree with standard tables presented in [4][5][6][7]. We hope that the MATLAB program presented here will be a useful addition to the existing software on numerical integration.…”
Section: Resultssupporting
confidence: 75%
“…However, we succeeded in determining zeros up to 32 digits accuracy by using the powerful built-in function solve (…..) available in the MATLAB programming. For even values of n, we have n/2 pairs of abscissas with opposite signs, while for odd values of n, there are pairs and hence only half the values need to be tabulated in tables of weights and abscissas of Gauss Legendre quadrature formulas, such tables are available in [4][5][6][7]. They are printed with 15-digits of accuracy for orders 2, 3, 4, 5, 6, 7, 8, 9, 10, 12.…”
Section: Theoremmentioning
confidence: 99%
“…(1) which, just as the density of the incident radiant flux, is approximated by the Gauss quadrature formula [21] at each point of the computational region (i = 1 ... N p ):…”
Section: Brief Review Of Modern Methods Of Solving the Radiative-tranmentioning
confidence: 99%
“…Computations necessary for determining the point locations and the weights were done by Lowan, Davids, and Levenson [24]. The result is that…”
Section: Linearly Polarized Incident Wavementioning
confidence: 99%